Clitoria ternatea Increases Milk Production in Dairy Cows by Inhibiting Dopamine Receptor D2: A Computational Study - Leondro, Henny; Hadiani, Dimas Pratidina Puriastuti; Krisnaningsih, Aju Tjatur Nugroho; Lestari, Oke Anandika; Wahyudi, Didik; Gusmalawati, Dwi; Tribudi, Yuli Arif; Prihandini, Peni Wahyu (Indonesian Journal of Chemistry, 2024)
Dairy cow's milk is a primary commodity in various countries and increasing milk production in dairy cows is crucial. Clitoria ternatea has the potential to enhance milk production in dairy cows. This research aims to analyze C. ternatea's ability to induce milk production in dairy cows by targeting the DRD2 protein. The compounds within C. ternatea were screened for drug-likeness, toxicity, physicochemical properties, and membrane permeability parameters. The DRD2 protein in dairy cattle was modeled using homology modeling. The interaction stability between C. ternatea compounds and DRD2 was analyzed through molecular docking and dynamic using AutoDock Vina and Webgro. The study results revealed that among the 18 compounds, 5 passed the drug-likeness screening: citronellal, alpha-terpinolene, 15-methyxypaysine, allyl-crotyl-zinc, and 9,12-octadecadiynoic. These 5 compounds exhibited low toxicity and demonstrated easy penetration of lipid membranes. Molecular docking results indicated that citronellal and alpha-terpinolene had the lowest binding energy values and were bound to the inhibitor's side. Molecular dynamic simulations also confirmed the stability of the interaction between citronellal and alpha-terpinolene with DRD2. In conclusion, this research suggests that C. ternatea can potentially increase milk production in dairy cows by inhibiting the DRD2 protein, primarily through citronellal and alpha-terpinolene.